Settlement of Land Disputes with the Competence of the State Administrative Court According to the Perspective of Indonesian Law - Jean Claudia (Pelopor Publikasi Akademika, 2023)
In the settlement of land disputes in each region, the characteristics are always different. In undeveloped areas, land dispute resolution is generally carried out by community leaders who are respected by local residents, namely customary heads or village heads. It can be said that cases of disputes in the land sector never subside; in fact, they tend to get more complicated and cause many problems, in line with Indonesia's economic, social, and political dynamics. The emergence of cases of land disputes in Indonesia lately seems to restate the fact that during Indonesia's independence, the state was still unable to guarantee land rights to its people, and the UUPA (Basic Agrarian Law) was only limited to marking the start of a new era. Land ownership, which was originally open and gradually developed into individual ownership, In this study, a normative juridical type was used through library research to identify and analyze legal factors that became obstacles in the application of laws and regulations, referring to laws and regulations on land and state administrative justice, court decisions, and other legal materials.